Education, Equity and Social Cohesion: A Distributional Model. Wider Benefits of Learning Research Report - Green, Andy; Preston, John; Sabates, Ricardo (The Centre for Research on the Wider Benefits of Learning, Institute of Education, 20 Bedford Way, London WC1H 0AL (5 British pounds), 2003)
The effects of education on social cohesion at the societal level were examined. First, a theoretical analysis and critique of models in the existing international and comparative literature on education, social capital, and social cohesion was conducted. The analysis resulted in development of a new hypothetical model relating skills distribution to social cohesion. Cross-national, quantitative research techniques were used to test the model on aggregated data for 15 countries from the World Values Survey, International Adult Literacy Survey, and Interpol crime statistics. The analysis established that societal cohesion is different, although related, to the community-level cohesion typically investigated in social capital research. The new "distributional" model therefore hypothesized a relation between education and societal cohesion based on distribution of educational outcomes rather than average levels of education. The analysis based on the new model established that Germany, Portugal, and the United States have the lowest scores on social cohesion, and the Netherlands, Denmark, and Norway have the highest. Measures of inequality in educational outcomes were higher in English-speaking countries and in some northern continental and Nordic countries. The analysis confirmed the hypothetical relationship between educational equality and societal cohesion. (Eight figures/tables are included. The bibliography lists 93 references. An explanation of the country indicators' derivation is appended.) (MN)
Keywords: Access to Education; Comparative Education; Crime; Developed Nations; Educational Attainment; Educational Research; Equal Education; Foreign Countries; Literature Reviews; Models; Multivariate Analysis; Outcomes of Education; Research Methodology; Role of Education; Skill Development; Social Capital; Social Integration; Social Science Research; Sociology